Insuring against the weather - Berhane, Guush; Clarke, Daniel J.; Dercon, Stefan; Hill, Ruth Vargas; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2013)
Weather risk remains a major challenge to farming in poor countries that face frequent droughts. Recent evidence on index-based weather insurance points to low take-up rates largely due to basis risk (i.e. residual risk left uninsured by the index). Using randomized control trials, we study to what extent traditional groups can be utilized to mitigate basis risk by retailing insurance through these groups. We find that selling insurance through iddirs, with pre-defined sharing rules, increases take-up—suggesting that groups are better placed to reduce basis risk. We also find that insurance strengthens existing risk-sharing behavior within groups, for example, by improving access to loans from the iddir to cover crop losses and improving perceived ability to finance emergencies. Insurance has also improved household welfare in the short term considered in this study, albeit to a limited extent.